Pengaruh Variasi Nutrisi dan Media Tanam terhadap Pertumbuhan Serta Hasil Selada (Lactuca sativa L.) dalam Budidaya Hidroponik Metode Deep Flow Technique (DFT) - Faridatul Munawaroh; Iskandar Umarie; Insan Wijaya (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Vegetables provide various essential nutrients, such as vitamins, fiber, calcium, iron, and carotene, which are very important for human health. Lettuce (Lactuca sativa L.) is a high-value commodity among many types of vegetables due to its exceptional nutritional content, especially vitamins A, B, C, and calcium. Because it uses less land and produces high-quality products, hydroponic lettuce cultivation is a good alternative. DFT (Deep Flow Technique) is one of the most widely used hydroponic cultivation methods. It allows for shorter harvest times and optimal yields, but requires careful management of nutrients and energy. This study focused on the impact of media and nutrient solution composition combinations on the growth dynamics and production of lettuce cultivated using the Deep Flow Technique (DFT) hydroponic approach. For this project, a Completely Randomized Design (CRD) was used, which had a split-plot design consisting of two factors and three replications. Nutrient type (N) was the first factor, and growing medium (M) was the subplot factor. Analysis of variance (ANOVA) was used to analyze the data, and this study used plant height, plant leaves (number, width, and length), root length, stem diameter, and fresh plant weight as observation parameters. Based on the experimental results, it was found that, compared to NPK application, the use of AB Mix significantly increased all growth parameters, including fresh weight. However, cocopeat and charcoal husk growing media produced the highest lettuce biomass, followed by rockwool. Conversely, rice husk and sawdust media produced the lowest growth results.